Isotope effects H/D in a PEFC with PtRu/anode at low and high current density. (15th March 2019) - Pozio, A.; Tosti, S.
Abstract: This paper reports a study on the use of a polymer electrolyte fuel cell (PEFC) with a PtRu/C anode for isotopic separation of hydrogen (H) and deuterium (D). The performance of a PEFC, fed with pure hydrogen, deuterium or a their mix is depicted. In order to investigate the effect of the two isotopes, electrochemical impedance spectroscopy (EIS) tests have been carried out together with galvanostatic polarization and IR analysis. Results evidenced an isotope effect on the thermodynamics, conductivity, ionic mobility and cathode mass transfer. IR analysis at the cathode side indicated that the isotopic separation efficiency was dependent on the current density with a maximum at intermediate values. Highlights: We analysed the isotopic separation factor of hydrogen (H) and deuterium (D) in a PEFC with PtRu/anode. We tested the PEFC through electrochemical impedance spectroscopy (EIS) and IR analysis. We verified the isotope effect based on the thermodynamics, conductivity, ionic mobility and cathode mass transfer. The isotopic separation efficiency was dependent on the current density with a maximum at intermediate values.